Preparation, characterization, and structural analysis of d8 palladium and platinum compounds containing amino acid ester derivatized diimine ligands. Observation of liquid crystal behavior. Issue 20 (18th October 2017) - Herrick, Richard S.; Ziegler, Christopher J.; Ding, Tang; Shaw, Janet; Wrona, Iwona; Beaver, Matthew; Giguere, Joshua; Maus, Caroline; Müller, Peter
Abstract: Eight new compounds, M(pyca(CH2 )x COOR)Cl2, M = Pd, Pt; R = Me, Et; x = 2, 3, 5, 11, were prepared. The resulting new complexes were characterized by 1 H and 13 C NMR spectroscopy and each was also structurally elucidated by X-ray crystallography. The compounds share general structural features, but there are differences in the alignment of the alkyl chain; as the chain lengthens, the chain straightens relative to the plane of the metal complex. For the dodecanoic ester derivatives, a nearly linear alkyl chain was observed. These longer alkyl derivatives show mesogenic behavior. Abstract :